Peculiarities of lymphotropic antibioticotherapy in a combat trauma of abdominal organs (clinic-experimental investigation) - І. D. Duzhyi; V. V. Shimko; G. І. Pyatikop; M. G. Kononenko; G. P. Oleshchenko; D. A. Al Yamani Navras (Клінічна хірургія)
Objective. Studying of impact of regional lymphotropic antibacterial therapy on various abdominal organs and application of the results in a combat abdominal trauma.